The Impact of Profitability, Institutional Ownership, and Managerial Ownership on Dividend Payout in Indonesian Energy Sector - Keisha Justina Siagian; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study investigates the determinants of dividend payout policy in energy sector firms listed on the Indonesia Stock Exchange during the 2020–2024 period. Dividend policy is a critical issue in emerging markets, especially in capital-intensive industries with high investment needs and earnings volatility. The research examines whether profitability and ownership structure—specifically institutional and managerial ownership—significantly influence dividend payout decisions, considering firm characteristics. The study analyzes the effect of profitability, institutional ownership, and managerial ownership on the dividend payout ratio, while controlling for firm size and leverage. A quantitative approach is used, employing pooled ordinary least squares (OLS) regression on 245 firm-year observations. Dividend payout ratio is measured as dividend per share divided by earnings per share, profitability is proxied by return on equity, and ownership variables are expressed as shareholding proportions. Descriptive analysis and classical assumption tests precede hypothesis testing. The results show that profitability positively and significantly affects dividend payout, suggesting that firms with better financial performance tend to distribute higher dividends. Firm size also positively influences dividend policy, while leverage negatively impacts it, reflecting the role of financial capacity and capital structure. However, institutional and managerial ownership do not show significant effects on dividend payout decisions. The findings indicate that dividend policy in Indonesian energy firms is primarily driven by financial performance and structural characteristics rather than ownership-based governance mechanisms. This study offers sector-specific evidence that refines agency and signaling perspectives on dividend policy in emerging markets, with practical implications for managers, investors, and regulators.